2016
DOI: 10.1515/ijb-2015-0074
|View full text |Cite
|
Sign up to set email alerts
|

Mendelian Randomization using Public Data from Genetic Consortia

Abstract: Mendelian randomization (MR) is a technique that seeks to establish causation between an exposure and an outcome using observational data. It is an instrumental variable analysis in which genetic variants are used as the instruments. Many consortia have meta-analysed genome-wide associations between variants and specific traits and made their results publicly available. Using such data, it is possible to derive genetic risk scores for one trait and to deduce the association of that same risk score with a secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 25 publications
1
66
0
Order By: Relevance
“…Although the two approaches address similar questions of identifying the link between height and osteosarcoma, the estimates obtained from the two approaches have different interpretations 50 . The former, an estimate of osteosarcoma risk associated with height-related genetic variants, aims more generally to determine common biological mechanisms between the two phenotypes while the latter, an estimate of osteosarcoma risk due to height, requires that additional assumptions be satisfied for the estimate to be valid.…”
Section: Discussionmentioning
confidence: 99%
“…Although the two approaches address similar questions of identifying the link between height and osteosarcoma, the estimates obtained from the two approaches have different interpretations 50 . The former, an estimate of osteosarcoma risk associated with height-related genetic variants, aims more generally to determine common biological mechanisms between the two phenotypes while the latter, an estimate of osteosarcoma risk due to height, requires that additional assumptions be satisfied for the estimate to be valid.…”
Section: Discussionmentioning
confidence: 99%
“…However, Thompson et al [21] showed that 2nd order weights produce causal estimates which are generally more biased than using 1st order weights. The reason for this apparent paradox is that 2nd order weights can be highly correlated with the ratio estimates themselves.…”
Section: Heterogeneity Assessmentmentioning
confidence: 99%
“… trueβ^=j=1Mtrueβ^jfalse/Vjj=1M1false/Vj. When s j , the standard error of trueγ^j, is negligible, the variance, V j , of trueβ^j can be estimated by Sj2false/trueγ^j2. The delta method can be used to obtain estimates of V j that allow for the uncertainty in trueγ^j, but these have to be used with care as such estimates are correlated with the estimate of trueβ^j and this correlation can introduce its own bias into trueβ^ …”
Section: Meta‐analysis Of Variant‐specific Estimatesmentioning
confidence: 99%
“…To harness these data, researchers have started to adopt a two‐sample design in which the variant‐exposure information comes from one GWAS and the variant‐outcome information comes from a second GWAS. () Such data provide valid MR estimates provided that the variant‐exposure relationship is the same in both study populations and, of course, that the other MR assumptions hold for all of the variants. This means that we need to be confident that none of the variants has a pleiotropic effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation